A new method of determining iron, nitrites, etc. - Calvin, John Willard (My University, 1906)
Introduction: In the experiments reported below an effort was made to determine substances such as ferrous iron, nitrites, etc., that reduce hydrogen peroxide quantitatively, by titrating them directly against a standard solution of hydrogen peroxide, using a titanium solution as an indicator. It was to determine whether or not it is possible to use a titanium solution as an indicator to show when the oxidation is complete, that the experiments were taken up. The fact that a yellow or orange color is produced when hydrogen peroxide is added to a titanium solution, was discovered by Schonn, and has long been known as a delicate test for both hydrogen peroxide and titanium. Although this reaction has been known about thirty years, in examining the literature on the subject, very little is found. In the Journal of the Chem. Soc., 1874, the yellow or orange color formed when a solution of titanium, made by digesting titanium oxide in concentrated sulphuric acid, is added to a solution of hydrogen peroxide, is given as a delicate test for the latter. In the Chemical News, Vol. 47, Edward Jackson gives an article in which he says in substance, if hydrogen peroxide is added to a solution of the chloride or sulphate of titanium, a fine yellow color is formed which is a delicate test for both the peroxide and titanium; the test being so delicate that 1 50,000th part of titanium or 1 25,000th part of hydrogen peroxide is sufficient to produce the color. In an abstract in the Journal of the Chem. Soc. from the Ber. d. Deutsch Chem. Ges., 1882, Weller gives a method of determining small amounts of titanium colorunetrically by means of the yellow color produced when hydrogen peroxide is added to the solution of titanium. The color produced in the unknown solution is compared with that produced by a standard solution made by dissolving pure potassium titanofluoride.
Citation: Calvin, John Willard. A new method of determining iron, nitrites, etc.. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Chemistry; Nitrites; Iron; Hydrogen Peroxide; Titanium; Chemical Engineering; Theses